RIGHT OF RETENTION OF POSSESSION AS A REAL RIGHT OF ENSURING THE CLAIM IN SERBIAN AND COMPARATIVE LAW (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The author discusses the problem of determining the legal nature of retention of possession (ius retentionis), as one of the most controversial issues in legal doctrine in relation to this civil law institute. The research sample in the work consists of: positive Serbian law; regulation of 11 European countries; two drafts that pretend to become the future civil law of the Republic of Serbia; and finally, the solution of the Draft Common Frame of Reference for European Private Law (DCFR), which is a potential framework for the future Serbian solution. By using a comparative and axiological method, the author concludes that the right place for retention of possession de lege ferenda is in the part of the law that regulates real rights, specifically the rights of real security of claims, instead of the Law on Obligations, which is now the case. He estimates that, although right of retention does not have all the elements of the rights of real guarantees (in particular, it lacks the right to follow the object), it nevertheless, functionally, with its object and effect, belongs to this group of subjective civil rights. For this reason, the author determines its legal nature as - sui generis real right of securing claims that is incomplete, and which is realized by authentic technique, through self-help.